2004
DOI: 10.1002/pi.1700
|View full text |Cite
|
Sign up to set email alerts
|

Electrosynthesis and characterization of o‐phenylenediamine oligomers

Abstract: The contribution of electrochemical methods to the development of conducting polymers has been most relevant, although the electropolymerization mechanism has not yet been totally elucidated. The formation of a high‐density oligomeric region in the electrode–solution interface has been clearly established as formed by oligomers with different chain lengths. It has been confirmed that, depending on the variables governing the process (applied potential, electrolysis time, concentration, etc), it is possible to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…The absorbance transient located at 460 nm is assigned to the intermediate of the phenazine-type dimmer/oligomer or the OPD cation radicals. The dimer and oligomer containing the phenazine-type have been reported to give the absorption bands at 420 nm and 451 nm, respectively [43,44]. The transients at 490 nm and 550 nm can be ascribed to the PANI-like dimer and oligomer intermediates, as shown in Scheme 1.…”
Section: In-situmentioning
confidence: 98%
“…The absorbance transient located at 460 nm is assigned to the intermediate of the phenazine-type dimmer/oligomer or the OPD cation radicals. The dimer and oligomer containing the phenazine-type have been reported to give the absorption bands at 420 nm and 451 nm, respectively [43,44]. The transients at 490 nm and 550 nm can be ascribed to the PANI-like dimer and oligomer intermediates, as shown in Scheme 1.…”
Section: In-situmentioning
confidence: 98%
“…The poor conductivities could be due to the deficiency of charge carriers on P o PD polymer backbone or due to the low mobility of carriers . In some previous studies, the conductivity values of P o PD films synthesized in aqueous medium were reported to be 4.3 × 10 −10 S cm −1 , 2.23 × 10 −7 S cm −1 in the presence of hydrochloric acid and 4.0 × 10 −7 S cm −1 , 2.9 × 10 −2 S cm −1 in the presence of sulfuric acid, respectively. In this study, the dry conductivity value of P o PD–CSA is five times less than that of P o PD–ClO 4 , which is due to the decreasing conjugation length of polymer chains or the size effect on mobility of counter anion (CSA − ) in polymer …”
Section: Resultsmentioning
confidence: 96%
“…P o PD, one of the most studied derivatives of polyaniline, has attracted much interest in recent years. Many studies related to P o PD have been carried out with respects to the polymerization mechanism, structure, stability, conductivity, redox transformation, and applications . Chiba et al suggested the structure of P o PD to be formed from the electropolymerization of o ‐phenylenediamine ( o PD) in an acidic aqueous medium, which was a ladder polymer with phenazine rings .…”
Section: Introductionmentioning
confidence: 99%
“…The ultraviolet–visible (UV–Vis, UV-1601, Shimadzu Corporation, Japan) spectrum of SAO ( Figure 3 D) shows a single peak at 285 nm, ascribed to the phenazine moieties formed [ 41 , 42 ] via strong π–π interactions [ 21 , 43 ]. The absence of peaks below 285 nm shows that the oligomers were not conjugated [ 44 ]. The low conductivity (2.04 × 10 −8 Scm −1 ) measured on the SAO also confirmed that the oligomers were not conjugated.…”
Section: Resultsmentioning
confidence: 99%